2013
DOI: 10.2310/jim.0b013e31828fcafb
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Correlation between Thyrotropin Receptor–Stimulating Antibodies and Bone Mineral Density in Postmenopausal Patients with Graves’ Disease

Abstract: Graves' disease is an autoimmune disorder with various clinical manifestations. Thyrotropin receptor antibodies (TRAbs), the circulating autoantibodies specific to Graves' disease, are the cause for hyperthyroidism, the most prevalent abnormality. Hyperthyroidism leads to increased bone turnover and a negative bone balance. The aims of the present study were to determine the relationship between TRAbs and bone mineral density (BMD), to assess the extent of BMD change in patients with Graves' disease, and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Bone mineral density was restored after successful stabilization of hyperthyroidism and the investigators concluded that the presence of TRAb could be a good marker of bone impairment during the hyperthyroid phase of Graves' disease. 27 In our investigation, TPOAb were found to be strongly linked with increased risk of any type of fractures, independently of TSH values. Women in whom TPOAb are present have lower BMD at the cytokines that also contribute to bone damage by potentiating the effects of RANK-RANKL signaling.…”
Section: Discussionsupporting
confidence: 48%
“…Bone mineral density was restored after successful stabilization of hyperthyroidism and the investigators concluded that the presence of TRAb could be a good marker of bone impairment during the hyperthyroid phase of Graves' disease. 27 In our investigation, TPOAb were found to be strongly linked with increased risk of any type of fractures, independently of TSH values. Women in whom TPOAb are present have lower BMD at the cytokines that also contribute to bone damage by potentiating the effects of RANK-RANKL signaling.…”
Section: Discussionsupporting
confidence: 48%
“…Considering that the large portions of these patients still have TSH stimulating antibodies after reaching the remission status, the activated TSHR signaling might play a role in hyperthyroidism-related bone disease. Indeed, it has been reported that TSH stimulating antibody levels are positively correlated with bone turnover marker levels and negatively correlated with bone mineral density [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, previous studies have confirmed that TRAb plays a very important role in bone metabolism. These studies, conducted on both males and pre- or postmenopausal women, have consistently found a negative correlation between TRAb titers and bone mineral density [ 22 24 ]. Moreover, Kumeda et al [ 25 ] have reported a close association between TRAb and bone metabolic markers in Graves' disease.…”
Section: Discussionmentioning
confidence: 99%